HUBUNGAN ANTARA BUDAYA ORGANISASI, STRES KERJA DENGAN KINERJA GURU DI SMA - Supardi Supardi; Rambat Nur Sasongko; Safnil Safnil (Manajer Pendididikan, 2017)
The purpose of this research is to analysic the corelation between  organization culture,  work stress and teacher performance. The reseach research were teachers i of senior high school No 1 Ulok Kupai. Samples were taken  35  teachers from senior high school. The data were  analysed with descriptive statistic inferensial and technique. Result of the research show that: (1)the is positive and significan corelation between organization culture  of teacher performance.(2)the is  positive and significan corelation between works stress of teacher performance. (3)there is positive and significan corelation between organization culture and work stress  of  teacher performance. To improve teachers quality, education and tranning is necessary